2008
DOI: 10.1007/s11325-008-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and risk of obstructive sleep apnea in primary care patients in Jordan

Abstract: Obstructive sleep apnea, snoring, and daytime sleepiness were common among Jordanian patients attending primary care clinics. More attention to OSA is needed in primary care, and patients at risk should be referred for further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 23 publications
5
42
3
4
Order By: Relevance
“…Our study represents a crude estimated prevalence rate of 4.98% of sleep apnea symptoms in our population, which is lower than reported in the US population based study presented on The National Sleep Foundation poll, using the Berlin questionnaire [10], and it is lower than prevalences reported for Pakistan [14] and Jordan [15].…”
Section: Discussioncontrasting
confidence: 61%
“…Our study represents a crude estimated prevalence rate of 4.98% of sleep apnea symptoms in our population, which is lower than reported in the US population based study presented on The National Sleep Foundation poll, using the Berlin questionnaire [10], and it is lower than prevalences reported for Pakistan [14] and Jordan [15].…”
Section: Discussioncontrasting
confidence: 61%
“…Participants were adults aged 20 to 59 years (Khassawneh et al 2009) with a confirmed HIV-positive serology (for cases) attending the HIV/AIDS Treatment Centre of the study site and clinically stable enough to participate in the study. Were excluded all PLWHA known to be obese (BMI ≥30 kg/m 2 ) prior to HIV diagnosis as well as pregnant women, demented patients, people with abnormal sleep-wake cycles due to night-shift work and all individuals who were on or had taken sleep inducing medications, or stimulants during the three months preceding the study.…”
Section: Study Participantsmentioning
confidence: 99%
“…In Jordan, the overall risk for OSA was 16.8% (19.3% men versus 14.7% women, resp., p < 0.04) [18]. In a general population surveys in Iran for investigating people at risk of OSA (using Berlin questionnaire), the surveyors found that 27.3% of subjects (men 19%; women 8.3%) were at high risk for OSA [19].…”
Section: Prevalence Of Osahs In the Middle East And Uaementioning
confidence: 99%